Patterns of Training Evaluation Practices among Training Institutions in Malaysia - Hashim, Junaidah (1999)
Experience has shown that one of the most effective ways trainers can improve their effectiveness and the training activities, In which they involved, is through evaluation evaluation is a systematic process of collecting and analyzing information for and about a programme which can be used for planning and guiding decision making as well as assessing the relevance, effectiveness and the impact of various programme components evaluation in training is an elusive concept especially when it comes to practice, there still appears to be more talks than action this criticism is largely explained by the unsystematic, Informal and ad-hoc evaluation been conducted by training Institutions. In Malaysia, training activities are monitored by the government agency called Human Resources Development Council Organisations are required to obtain training services from the training institutions that registered with the Council, In order to enable the organisations to get reimbursement for their training expenditures There is no study has been conducted to examine the practice of evaluation In training among these training Institutions this study examined the background characteristics of training evaluators, practices of evaluation In training, and identified the patterns of commonalities governing the practice.